Proposal of a novel reference system for the green product development process (GPDP). (20th June 2018) - de Medeiros, Janine Fleth; Lago, Nicole Cecchele; Colling, Camila; Ribeiro, José Luis Duarte; Marcon, Arthur
Abstract: This study aimed to investigate the alignment between environmental sustainability and the product development process of Small and Medium-sized Enterprises that operate in Southern Brazil, as well as to propose a system to assist the execution of a green product development process. To that end, an exploratory research was carried out in two steps: (i) narrative bibliographic review and (ii) a field research. The (i) bibliographic review was conducted in the "Web of Science" and "Scopus" databases. The (ii) field research was executed with managers of 18 industries of different segments. Regarding the theoretical research, results show the state-of-the-art in academic research on product development process and sustainability practices, which provided support for the design of the data collection instrument and for the reference system suggested at the end of the work. As to the field research, results show that the sampled organizations understand the need for product and process environmental sustainability and they define internal drivers for the adoption of adequate practices, adapting such practices to the regulatory pressures and to market demands. Nevertheless, environmental matters do not comprise a dominant topic on product development. In this sense, we propose a reference model that aims to support companies to strategically align environmental aspects to the product development process. Although literature describes specific reference models, the need for a new system is justified since previous models presented specificities, lacked both post development assessment phases and introductory phases of product planning before the conceptual design. Therefore, the reference system proposed present phases that precede the development process (Sustainability-Oriented Organizational Strategic Planning; Portfolio Strategic Planning; and Project Strategic Planning), followed by the development phases (Operational Planning of the Product; Production Preparation; and Product's Launch Plan), and one post-development phase (Market Follow-Up of the Product). Future studies can apply the model in real cases through the action research method. Highlights: Green PDP depends on a sustainability-oriented organizational strategic planning. Our research focuses on the green PDP of Small and Medium-sized Enterprises (SMEs). We apply a theoretical and a field research to map green PDP literature and practices. We propose a reference system to integrate ecological tools in the green PDP of SMEs. The system proposes the inclusion of pre and post development steps in the green PDP.